Detailization of the Facial Conditions for Sedimentation of the 〖Yu〗_1^2 Productive Layer with the Purpose of Specificating Features of the Geological Structure - ALEKSANDROV, SorinVadim M.; MOROZOV, Alexander V.; POPOV, Ivan P.; LEBEDEVA, Rushania G.; BULGAKOVA, Irina A. (Journal of Environmental Management and Tourism; Vol 9 No 5 (2018): JEMT Volume IX Issue 5(29) Fall 2018DO - 10.14505//jemt.v9.5(29).05, 2018)
The detailed characterization of the environmental conditions of sedimentation of the   productive formation makes it possible to refine the features of the geological structure. The authors carried out a detailed lithologic-facial analysis of the deposits of the Yu 1 2 productive formation at one of the deposits located in the southeastern part of the West Siberian oil and gas basin. Detailed lithologic-facial schemes were constructed that reflect the spatial distribution of the main permeable bodies, considering the forecast of the distribution of promising reservoir rocks in zones not covered by drilling. The well test results confirm the adopted model of sedimentary facies distribution over the area of the deposit. The proposed conceptual model was used to construct a three-dimensional facial model of the deposit. Thus, a detailed lithologic-facial analysis of the core and forms of the GIS curves showed that deposits of the  stack accumulated in coastal-marine sedimentation environments – "marshes" and "watts", repeatedly replacing each other vertically.